Analisis Aktivitas dan Hasil Belajar Siswa Dalam Pembelajaran Fisika Menggunakan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Materi Elastisitas - Putri, Happy Vilianti; Putri, Desy Hanisa; Setiawan, Iwan (Jurnal Penelitian Pembelajaran Fisika, 2023)
The Numbered Head Together (NHT) cooperative model is a type of learning that can increase student and teamwork in learning process. The purpose of this study is to describe of students activities and studensâ€™ learning outcomes in physics learning of the NHT cooperative learning model. Research done at SMA Negeri 3 Bengkulu City, Bengkulu Province. The research sample in this study were 33 students of c class XI MIPA 1. The technique used to determine the research sample is random sampling. The research steps include preparation (initial observation, interview preparation of rencana pelaksanaan pembelajaran (RPP), activity observation sheets), implementation, and analysis. The research instrument is a activity observation sheets containing 18 statements. Data is analyzed quantitatively using IBM SPSS 25 software. Based on data analysis in the study, it was concluded that students' learning outcomes were in the very high category and students activities in physics learning of the NHT cooperative learning model is very good category.Â Keywords: Cooperative, Numbered Head Together, ActivitiesÂ